1997
DOI: 10.1002/(sici)1099-1166(199711)12:11<1062::aid-gps675>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour changes in dementia 1: Point of entry data of a prospective study

Abstract: Objective. This article analyses behaviour changes in dementia at the point of entry to a longitudinal study. Design. Prospective, longitudinal study of behaviour in dementia, with autopsy follow‐up. Setting. Subjects with dementia, living at home with a carer. All lived in Oxfordshire, UK. Participants. Ninety‐seven people with dementia (Alzheimer's disease and/or vascular dementia) who were living at home with a carer. Measures. At 4‐monthly intervals, the carers were interviewed and the subjects with dement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
60
1

Year Published

1998
1998
2005
2005

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 30 publications
4
60
1
Order By: Relevance
“…A total of 42 individuals were included in the study, 21 patients with a clinical diagnosis of dementia and 20 elderly normal control cases. Those patients with dementia were an autopsied subset of subjects included in a prospective study of behavioral changes in clinically diagnosed demented patients (Hope et al, 1997). Initially, all patients were living in community with a caregiver (usually spouse or daughter) who could accurately report day-to-day behavior.…”
Section: Patients and Assessment Of Behaviormentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 42 individuals were included in the study, 21 patients with a clinical diagnosis of dementia and 20 elderly normal control cases. Those patients with dementia were an autopsied subset of subjects included in a prospective study of behavioral changes in clinically diagnosed demented patients (Hope et al, 1997). Initially, all patients were living in community with a caregiver (usually spouse or daughter) who could accurately report day-to-day behavior.…”
Section: Patients and Assessment Of Behaviormentioning
confidence: 99%
“…Four behavioral and psychological syndromes were assessed using the Present Behavioral Examination (PBE) (Hope and Fairburn, 1992): depression, overactivity, psychosis, and aggressive behavior (Hope et al, 1997). Briefly, the PBE is a standardized, caregiver-based interview with high intra-and inter-rater reliability that covers in detail the observable behavior and mental state of the patient.…”
Section: Patients and Assessment Of Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…increase as the dementia progresses (Hope et al, 1997;Hwang et al, 1997;Rubin et al, 1987;Teri et al, 1988). Teri and coworkers (1988) observed that only 8% of the mildly demented patients they examined exhibited three or more behavior problems, compared to 88% of patients with severe dementia.…”
mentioning
confidence: 98%
“…Those patients with dementia were an autopsied subset of subjects included in a prospective study of behavioural changes in clinically diagnosed as demented patients [16]. Cognitive status was assessed at 4 monthly intervals using the mini-mental state examination (MMSE) [8].…”
mentioning
confidence: 99%